2002
DOI: 10.1007/s10152-002-0105-3
|View full text |Cite
|
Sign up to set email alerts
|

Feeding rates and selectivity among nauplii, copepodites and adult females of Calanus finmarchicus and Calanus helgolandicus

Abstract: This study focuses on selective feeding by developmental stages of two oceanic copepods, Calanus finmarchicus and Calanus helgolandicus from nauplii to adults. A mixture of four algal species of different biochemical composition, Prorocentrum nanum (dinoflagellate), Thalassiosira minima (diatom), Rhodomonas baltica (cryptophyte) and Dunaliella tertiolecta (chlorophyte), added in an equal biovolume, was used in three different experimental set-ups. In set-up 1 the algal species were present as single cells of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…20 cells (Smayda and Boleyn 1966), and such chain length plasticity may provide an effective refuge from size-dependent grazing. It has previously been shown that grazing rates of copepods in the genus Calanus were higher on diatom chains than on singlecelled diatoms (Richman and Rogers 1969;Meyer et al 2002). These size-related changes in grazing impact may thus have large effects on pelagic ecosystems and energy flows, especially when found among ecologically dominant species (Smayda and Boleyn 1966).…”
mentioning
confidence: 98%
“…20 cells (Smayda and Boleyn 1966), and such chain length plasticity may provide an effective refuge from size-dependent grazing. It has previously been shown that grazing rates of copepods in the genus Calanus were higher on diatom chains than on singlecelled diatoms (Richman and Rogers 1969;Meyer et al 2002). These size-related changes in grazing impact may thus have large effects on pelagic ecosystems and energy flows, especially when found among ecologically dominant species (Smayda and Boleyn 1966).…”
mentioning
confidence: 98%
“…Specific filtration rates set to 14 and 18 mL/mm/day for the low and high prediction, respectively, for an approximate fit. Right panel measured ingestion rates (Meyer et al 2002) versus volumetric length (calculated from reported C content, for stage N4/5-adult). Model predictions using two values for the scaled functional response, the lower estimate providing an approximate fit to the data …”
Section: Resultsmentioning
confidence: 99%
“…Data on filtration and ingestion rates for different stages were taken from Marshall and Orr (1956) and Meyer et al (2002). Data were extracted from the graphs in the original publications using the freeware PlotReader (http://jornbr.home.xs4all.nl/plotreader).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between the last nauplius (NVI) and the first copepodite (CI) stage there is high mortality (Peterson 2001) associated with major morphological modifications, which include changes in swimming and feeding behavior, changes in the sensory system, and a reorganization of the nervous system (Paffenhöfer and Lewis 1989; Peterson 2001; Wilson and Hartline 2011). These changes have stoichiometric implications: body carbon-specific ingestion rates of nauplii are high and typically exceed 100% of body C per day (Meyer et al 2002; Henriksen et al 2007; Jungbluth et al 2017), while those of adult copepods are below 30% of body C per day (Meyer et al 2002). Furthermore, C:N ratios are lower in nauplii than copepodites (Campbell et al 2001).…”
Section: Discussionmentioning
confidence: 99%